2011
DOI: 10.1111/j.1600-0846.2011.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Sun‐induced changes of stratum corneum hydration vary with age and gender in a normal Chinese population

Abstract: These results demonstrated that sun-induced changes of the SC hydration property vary with age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…These localization-dependent differences are probably influenced by the higher sun exposure of the face and neck. This presumption was confirmed by Liu et al [31], who showed that cumulative sun exposure does reduce SC hydration, probably due to a UVB-induced downregulation of epidermal ceramides, fillagrins and aquaporins [32,33,34,35]. …”
Section: Discussionsupporting
confidence: 68%
“…These localization-dependent differences are probably influenced by the higher sun exposure of the face and neck. This presumption was confirmed by Liu et al [31], who showed that cumulative sun exposure does reduce SC hydration, probably due to a UVB-induced downregulation of epidermal ceramides, fillagrins and aquaporins [32,33,34,35]. …”
Section: Discussionsupporting
confidence: 68%
“…HA is known to play a key role in maintaining the water content of the skin. Previous reports have described an age‐related variation in hydration levels between the SC and dermis . We observed an age‐related difference in the hydration patterns between the epidermal and dermal layers of skin.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, keratinocytes derived from different sites can serve as general keratinocyte model systems. Taken together, the results on primary keratinocytes were counterintuitive considering constitutional factors on the one hand and studies that have demonstrated varying skin functions (15)(16)(17)(18)(19)(20) on the other hand. Our results suggest that involvement of keratinocytes is only small in skin functions dependent on age, gender, or localization and that their main function comprises formation of a barrier against environmental insults.…”
Section: A431 Cells Exhibit Decrease In Stromal Communication Increamentioning
confidence: 66%
“…However, the short keratinocyte life cycle of about 4 weeks requires a steady supply of fresh tissue samples, and a concern is that varying constitutional factors such as age, gender, and anatomic site may compromise experimental results. Many skin properties have been examined with respect to such factors and an impact has been observed on epidermal thickness (15), epidermal nerve fiber density (16), skin surface pH (17), protein absorption ability (18), stratum corneum hydration (17,19), melanin index, and skin elasticity (20). These properties arise from the interplay of many cell types in the tissue context, most importantly between dermal fibroblasts and epidermal keratinocytes.…”
mentioning
confidence: 99%